Disintermediation of Fresh Fish Distribution: Analysis of Online Market Efficiency and Logistics Barriers in Makassar City - Hasani, M. Chasyim; Nurjannah, Nurjannah (SIGn Journal of Social Science, 2025)
The acceleration of digital economic transformation in the national fishery sector offers potential for allocative efficiency by shortening conventional supply chains, yet its implementation often clashes with the reality of stagnant physical infrastructure. This study aims to analyze disintermediation mechanisms arising from online market adoption, evaluate the efficiency of cold chain logistics, and formulate strengthening strategies for the integrative distribution system in Makassar City. Using a qualitative descriptive research design, data were collected via triangulation through field observations at physical distribution nodes in Paotere Fish Auction Market, transaction activity observations on marketplace platforms, and documentation studies, which were then analyzed using the interactive model by Miles et al. The results reveal a sharp logistics paradox. On the one hand, the online market successfully enabled disintermediation, increased price transparency, and severed fishermen’s dependence on traditional intermediaries. However, fundamental vulnerabilities were identified due to the absence of micro-scale cooling facilities and the use of non-standard last-mile delivery fleets. This condition results in accumulated risks of biological quality degradation and hidden operational cost inefficiencies. The study concludes that digital superstructure dominance without an adequate physical infrastructure foundation only yields pseudo-efficiency, threatening business sustainability. As a managerial implication, this study recommends implementing a hybrid logistics ecosystem through a Hub-and-Spoke model, transforming the Fish Auction Market into cold-chain-based fulfillment centers, supported by Public-Private Partnership policy synergy and the social engineering of fishermen’s logistics literacy.